2019
DOI: 10.1063/1.5064700
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic forces on projectiles used in various sports

Abstract: The aerodynamics of projectiles used in various sports is investigated via experiments in a low speed wind tunnel. Force measurements are carried out on actual artifacts at speeds in the range of 15-75 m/s. The sports considered include golf, field hockey, soccer, baseball, tennis, cricket, volleyball, and badminton. Both synthetic and duck-feather models of shuttle-cocks used in badminton are considered. The variation of the coefficient of drag, CD, with Reynolds number, Re, is quite different for the two mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The critical region (1.65 × 10 5 < Re < 1.75 × 10 5 ) is marked in Figure 3. The non-dimensional side force coefficients for CS (CZ~0.3) are comparable with the results of other studies on stationary balls [9,10]. Note that the magnitude of CZ for RS is less than that for CS either side of the critical Re (Recrit).…”
Section: Flow Separation On Spheres and Cricket Ballssupporting
confidence: 87%
See 1 more Smart Citation
“…The critical region (1.65 × 10 5 < Re < 1.75 × 10 5 ) is marked in Figure 3. The non-dimensional side force coefficients for CS (CZ~0.3) are comparable with the results of other studies on stationary balls [9,10]. Note that the magnitude of CZ for RS is less than that for CS either side of the critical Re (Recrit).…”
Section: Flow Separation On Spheres and Cricket Ballssupporting
confidence: 87%
“…They found that the critical flow regime can be further categorized into three sub-regimes based on the nature of the LSB. The method of PIV has not been used to identify the LSB on a cricket ball (rotating or nonrotating), but it has been used to show the boundary layer separation angles on a stationary sphere with a trip at the sub-critical and critical flow regimes, demonstrating CS and RS [10]. The image resolution of their system was too low to be able to resolve an LSB.…”
Section: Flow Separation On Spheres and Cricket Ballsmentioning
confidence: 99%
“…The non-dimensional side force data in the study by Shah et al 23 can be compared with the ‘new ball’ data the authors presented above. Over the range for CS (1.3 × 10 5 < Re < 1.7 × 10 5 ) Shah et al 23 measured a relatively constant C Z = 0.3, which agrees well with the data presented in Figure 10(b).…”
Section: Resultsmentioning
confidence: 99%
“…The non-dimensional side force data in the study by Shah et al 23 can be compared with the ‘new ball’ data the authors presented above. Over the range for CS (1.3 × 10 5 < Re < 1.7 × 10 5 ) Shah et al 23 measured a relatively constant C Z = 0.3, which agrees well with the data presented in Figure 10(b). The comparison is good despite differences in the seam angle to the flow (30° for Shah et al 23 ) versus 15° used here; also, the ball used in the study by Shah et al 23 was manufactured by SG , not Dukes .…”
Section: Resultsmentioning
confidence: 99%
“…They have been employed for measurement of time-varying forces by a number of researchers (Suryanarayana & Prabhu 2000; Deshpande et al. 2017; Shah, Shakya & Mittal 2019). The balance was installed inside the horizontal sting and connected directly to the rear part of the sphere.…”
Section: Experimental Set-up and Methodologymentioning
confidence: 99%